2000
DOI: 10.1097/00000539-200006000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Labor Epidural Analgesia: Bupivacaine Versus Ropivacaine

Abstract: As compared with a similar dilute concentration of bupivacaine, 20 mL of dilute (0.08%) ropivacaine combined with fentanyl (2 microg/mL) effectively initiates epidural analgesia in nulliparous women in early, established labor while preserving their ability to micturate and ambulate. Of importance, it appears that a true ambulatory epidural analgesic for women in labor is now possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
2
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 15 publications
5
30
2
2
Order By: Relevance
“…14 In a study utilizing 40 µg epidural fentanyl with 20 mL 0.08% bupivacaine, the analgesic duration was shown to be 91 ± 24 min. 15 These times are significantly less than the analgesia in our previous studies of epidural opioids, [1][2][3][4] as well as in the current study (135-145 min). However, Breen et al's study population included both primigravidous and multigravidous patients.…”
Section: Objectifcontrasting
confidence: 56%
“…14 In a study utilizing 40 µg epidural fentanyl with 20 mL 0.08% bupivacaine, the analgesic duration was shown to be 91 ± 24 min. 15 These times are significantly less than the analgesia in our previous studies of epidural opioids, [1][2][3][4] as well as in the current study (135-145 min). However, Breen et al's study population included both primigravidous and multigravidous patients.…”
Section: Objectifcontrasting
confidence: 56%
“…Fetocide was performed under patient-controlled epidural analgesia using ropicovaine (0.1%) and sufentanil (0.5 Ag/mL). This technique allowed for ambulatory analgesia during cervical maturation and first stage of labour 26,27 . The epidural level was adjusted if necessary to obtain a T8 level just before fetocide.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 10% of patients in Group B and 6.7% in Group R had intrapartum urinary retention (patients catheterized with K-90 catheter). Campbell et al [13] observed that ropivacaine (0.08%)/fentanyl group did not experienced urinary retention but 35% patients of bupivacaine (0.08%)/ fentanyl group experienced urinary retention.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%
“…In our study, no patients developed bradycardia or respiratory depression in either group. Campbell et al [13] observed that there was no incidence of hypotension in either group (bupivacaine (0.08%)/fentanyl vs. ropivacaine (0.08%)/ fentanyl) whereas Fernández-Guisasola et al [6] compared the 0.0625% bupivacaine with 0.1% ropivacaine with fentanyl as an epidural infusion and observed 2 patients in bupivacaine group and 1 patient in ropivacaine group required ephedrine for hypotension. In this study, there was no incidence of pruritus in either group.…”
Section: International Journal Of Medical Science and Public Healthmentioning
confidence: 99%